Synthesis, spectroscopic characterization, solvatochromic properties and DFT quantum chemical calculations of 3?-acetoxy-17?-(1-acetyl-5-(3-pyridinyl)-3-pyrazolinyl) androat-5-ene - Genc, Murat; Shehu, Abdulmalik; Servi, Suleyman (Elsevier, 2019)
In this study, 3 beta-acetoxy-17 beta-(1-acetyl-5-(3-pyridinyl)-3-pyrazolinyl) androat-5-ene (AAPP) was synthesized from the reaction of 21(E)-3 beta-acetoxy-21-(3-pyridinylidene)pregn-5-en-20-one with hydra-zine hydrate in acetic acid. The structure of the compound was confirmed by UV-vis, FT-IR, H-1 NMR and C-13 NMR spectroscopic techniques. Optimized geometries and experimental results were interpreted by using DFT (B3LYP/6-311 + G (d,p) method). The NMR spectrum was recorded in CDCl3 and the chemical shifts of hydrogen and carbon atoms were studied experimentally as well as theoretically. Electronic properties of a molecule such as global reactivity, the frontier molecular orbital analysis, natural bond orbital (NBO) analysis, absorption-emission characteristics of the molecule were studied. Kamlet-Taft and Catalan solvatochromism of synthesized compound have been analyzed. The solvatochromic behavior of the compound was evaluated with respect to their visible absorption properties in various solvents. The chemical reactivity indices and thermodynamic properties were also evaluated. (C) 2019 Elsevier B.V. All rights reserved.
Keywords: Steroid; DFT; Kamlet-Taft and Catalan